2014
DOI: 10.7314/apjcp.2014.15.20.9039
|View full text |Cite
|
Sign up to set email alerts
|

Immunopreventive Effects against Murine H22 Hepatocellular Carcinoma in vivo by a DNA Vaccine Targeting a Gastrin-Releasing Peptide

Abstract: There is a continuing need for innovative alternative therapies for liver cancer. DNA vaccines for hormone/ growth factor immune deprivation represent a feasible and attractive approach for cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Currently, liver cancer vaccines are primarily categorized as preventive and therapeutic types, with the main goal of initiating or enhancing the human body’s immune response against cancer. 28 Some preventive vaccines, such as DNA vaccines, 29 live-attenuated Listeria vaccines 30 and peptide vaccine 31 have shown effective preventive results. On the other hand, personalized peptide vaccines have demonstrated efficacy in postoperative liver cancer prevention, 32 but their effectiveness varies due to individual patient characteristics and the heterogeneity of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, liver cancer vaccines are primarily categorized as preventive and therapeutic types, with the main goal of initiating or enhancing the human body’s immune response against cancer. 28 Some preventive vaccines, such as DNA vaccines, 29 live-attenuated Listeria vaccines 30 and peptide vaccine 31 have shown effective preventive results. On the other hand, personalized peptide vaccines have demonstrated efficacy in postoperative liver cancer prevention, 32 but their effectiveness varies due to individual patient characteristics and the heterogeneity of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrin-releasing peptide promotes hepatocellular carcinoma cell growth not only by interacting with homologous receptors of gastrin-releasing peptide co-expressed in tumor cells but also by activating the mitogen-activated protein kinase/extracellular signal-regulated kinase 1/2 (MAPK/ERK1/2) pathway through a non-dependent mechanism of the epidermal growth factor receptor (EGFR) ( Savage et al, 2006 ), it can also inhibit the growth of normal liver cells by blocking the activation of ER ( Li et al, 2013 ). A DNA vaccine targeting gastrin-releasing peptide has been shown to inhibit the growth of blood vessels in liver tumors and to destroy tumor cells ( Meko’o et al, 2014 ; Stubbs et al, 2002 ). However, in cholangiocarcinoma, gastrin appears to have the opposite effect to that of hepatocellular carcinoma, inhibiting the proliferation of cholangiocarcinoma cells and inducing apoptosis via the Ca2+ dependent protein kinase C (PKC)-α pathway ( Kanno et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…CCK has functions that include stimulation of intestinal motility, stimulation of pancreatic enzyme secretion, and stimulation of gastric acid secretion ( Rehfeld, 2017 ). Its primary function is to trigger gallbladder emptying by binding to the CCK A-type receptor (CCKAR) and mediating the activation of post-membrane signaling pathways in smooth muscle, defects in CCKAR are a key point of impairment of gallbladder motility, which in turn may form the background for GBC ( Suzuki et al, 2001 ; Best Practice & Research Clinical Endocrinology & Metabolism, 2008 ), abnormal level of CCK results in reduced or delayed postprandial gallbladder contraction, leading to bile stagnation and creating an environment for cholesterol supersaturation and subsequent gallstone formation ( Savage et al, 2006 ; Meko’o et al, 2014 ; Stubbs et al, 2002 ; Kanno et al, 2001 ; Chau et al, 2006 ). Both CCK and its receptor CCKAR are important in the pathogenesis of biliary tract tumors, CCK is currently thought to exhibit growth-stimulating effects on biliary tract-derived cancer cell line ( Lee et al, 1989 ), an analysis of the biliary tract tumor in Shanghai, China, found that women with the CCKAR genotype were at increased risk of gallbladder cancer, and biliary tumorigenesis may be inhibited when CCKAR is in an antagonistic state ( Ogura et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, preventive vaccines have shown promising potential in the fight against HCC. One such example is a DNA vaccine targeting the B cell epitope GRP18-27, which demonstrated preventive effects against H22 hepatocarcinoma, paving the way for new immunotherapeutic approaches in liver cancer treatment [ 27 ]. Innovative approaches, such as using live-attenuated Listeria as a safe and efficient vaccine, have also shown the potential to induce protective immune responses in liver fibrosis and hepatobiliary malignancies [ 28 ].…”
Section: Cancer Vaccinementioning
confidence: 99%